Penulisan Tafsir Nusantara: Cabaran dan Penyelesaiannya: Nusantara Tafsir Writing: Challenges and Solutions - Ismail, Muhammad Tajudin; Mohd, Nor Syamimi (Al-Basirah Journal, 2024)
The number of Nusantara tafsir works available today is evidence of the hard work of Nusantara exegetes in conveying an understanding of the Quran to the community. The development of Nusantara tafsir writing is an important area of study, though it comes with its own unique challenges and requires specific approaches to address them. This study employs a library research method, examining literature that discusses common issues related to challenges in the study of Nusantara tafsir. One identified challenge is the lack of efforts to examine the intertextuality present in Nusantara tafsir books, which can be addressed by increasing incentives for researchers. Limited access to Nusantara tafsir sources and a lack of efforts to perform takhrij (critical assessment and verification) of these books also pose significant challenges for Nusantara tafsir researchers. The role of authorities and institutions is essential in expanding access for researchers to the original Nusantara tafsir sources and in providing greater incentives for takhrij, which requires a large, skilled workforce. Other challenges, such as language barriers and writing style, can be overcome by vernacularizing these books to a language style and dialect suitable for modern society. The lack of relevant learning technology also hampers the efforts to disseminate Nusantara tafsir writings and can only be resolved through a holistic approach, including the development of applications that can be utilized by the general public This study could be further improved with a more in-depth and targeted analysis of each of the listed challenges.